The Effect of Foreign Institutional Ownership, Foreign Directors and Foreign Commissioners on Profitability - Yulian Belinda Ambarwati (Universitas Hayam Wuruk Perbanas, 2021)
In 2018, the banking world became a hot topic of conversation because several foreign companies announced their plans to own shares in local banks in Indonesia. Merger between local banks and foreign banks will allow foreign workers to work in Indonesia. This study aims to examine whether foreign institutional ownership, foreign directors and foreign commissioners have an effect on profitability. The sample used in this research is banking companies listed on the Indonesia Stock Exchange in 2014-2018. The research method used is multiple regression analysis. The results of this study indicate that foreign institutional ownership has an effect on profitability. Acquisitions by foreign parties are considered to be able to improve the performance of local banks. Foreign-owned banks are associated with increased profits. Meanwhile, both foreign directors and foreign commissioners have no effect on profitability. The low number of foreign directors and commissioners makes their performance unnoticeable.